Availability of health care in the Regions of Lublin and Katowice in opinions of patients with diagnosis of pathology of uterine - Bojar, Iwona; Holecki, Tomasz; Wdowiak, Leszek (Polish Journal of Public Health, 2009)
Aim. The objective of the study was the comparison of opinions of patients with the diagnosis of uterine cervix pathology concerning the availability of gynaecologicalobstetric care in the Regions of Lublin and Katowice.Material and methods. The study was conducted in 2009, and covered randomly selected patients with the diagnosis of uterine cervix pathology, who had been referred to gynaecological wards for further diagnostics and treatment. The research tool was a questionnaire form. The participants of the study were 142 patients from the Lublin Region and 162 patients from the Silesian Region. The results obtained were subjected to statistical analysis.Results. A significant statistical difference in patients’ accessibility to care was observed between the Lublin and Silesian Regions. In both regions, the accessibility was evaluated as being on the mediocre level; however, patients in the Lublin Region evaluated it in more positive terms than in Silesia. The majority of patients indicated distant dates of appointments as the main problem hindering access to gynaecological care. Most often, patients waited for a visit to a gynaecologist from several days to one month. Cytological test results are available for a patient within one week to one month after the examination has been made. No regional differences were noted in this respect. In Silesia, patients received the referral to hospital diagnostics sooner; however, they waited longer for admission to hospital than patients from the Lublin Region.Conclusion. Short time intervals between cytological tests and the beginning of treatment evidences a relatively good access to diagnostic-treatment procedures related with pathologies of the uterine cervix. It is necessary to develop a national project which would provide incentives for women to participate in prophylactic examinations for cervical cancer regularly.